2023
DOI: 10.1038/s41541-023-00756-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the factors affecting waning of post-vaccination neutralizing antibody responses against SARS-CoV-2

Henning Jacobsen,
Ioannis Sitaras,
Maeva Katzmarzyk
et al.

Abstract: Mass COVID-19 vaccination and continued introduction of new SARS-CoV-2 variants increased prevalence of hybrid immunity at various stages of waning protection. We systematically reviewed waning of post-vaccination neutralizing antibody titers in different immunological settings to investigate differences. We searched published and pre-print studies providing post-vaccination neutralizing antibody responses against the Index strain or Omicron BA.1. We used random effects meta-regression to estimate fold-reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A longitudinal sampling from the same cohort/trial will be needed for a definitive conclusion. Previous studies have observed faster waning of titers against Omicron variants than against Anc./D614G after bivalent vaccination Jacobsen et al 2023;Chalkias et al 2022),.…”
Section: Xbb Infection Data Suggests That Flattening Of the Antibody ...mentioning
confidence: 89%
“…A longitudinal sampling from the same cohort/trial will be needed for a definitive conclusion. Previous studies have observed faster waning of titers against Omicron variants than against Anc./D614G after bivalent vaccination Jacobsen et al 2023;Chalkias et al 2022),.…”
Section: Xbb Infection Data Suggests That Flattening Of the Antibody ...mentioning
confidence: 89%
“…COVID-19 boosters in these individuals aim to reduce their occupational risk of infection and transmission to vulnerable populations. Bivalent boosters may provide protection against hospitalisation and severe symptoms caused by various SARS-CoV-2 variants [ 7 , 8 , 26 , 27 , 28 ], particularly in individuals with “hybrid immunity” [ 1 , 2 , 3 , 4 , 5 , 7 , 8 ]. Such boosters can enhance both humoral and cellular immunity, decrease infection rates, and offer protection, especially for specific populations such as organ transplant recipients, dialysis patients, individuals with chronic renal disease, the elderly population, and immunocompromised individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, individuals with “hybrid immunity”, resulting from both vaccination and infection, may experience enhanced protection against severe symptoms. This phenomenon is attributed to a broader recognition of different Ags not included in the vaccine design and the subsequent boosting of mucosal immunity [ 2 , 3 , 4 , 5 ]. The emergence of the Omicron variant (B.1.1.529) suggests that the spike protein of this viral variant may elicit broader SARS-CoV-2 protective immunity against the emerging variant(s) [ 1 ].…”
Section: Current German Recommendationsmentioning
confidence: 99%
“…This feature is unique for this vector and superior to other vaccine formulations, which require repeated booster administrations to avoid immune waning over time (47, 48, 52, 53). Considering that neutralizing antibodies against SARS-CoV-2 wane at similar rates upon infection or vaccination with currently used vaccines (9, 46, 54-56), our vaccine might provide an immunity that is even better than that induced by infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous COVID-19 vaccines that induce immune responses against the S glycoprotein have been developed and authorized for use with unprecedented speed. However, vaccine-induced immunity wanes within months, resulting overall in reduced protection against infections and disease (4, 7-9). In addition, emerging variants have been increasingly capable of escaping vaccine-induced immunity driving the need for continued vaccine adaptation and booster shots (10-12).…”
Section: Introductionmentioning
confidence: 99%